Effect of Salinity Adaptation Technique on Survival and Growth Rate of Patin Catfish, Pangasius sp. - K. Nirmala; D.P. Lesmono; D. Djokosetiyanto (Jurnal Akuakultur Indonesia, 2007)
This study was carried out to determine the effect of salinity adaptation techniques on growth and survival of patin catfish Pangasius sp. fry.  Fry of 1.5-2.0 inch in length were reared in the water with different of the initial salinity of 1, 2, 3, 4 and 5 ppt.  Salinity was then daily increased by duplicated the initial water salinity until fish died.  The results of study showed that fry could survive by initial salinity adaptation of 1 ppt and then increasing the salinity by 1 ppt/day to reach 27 ppt.  In the other treatments, all fry died after the salinity reach 18-25 ppt.